Modern Lens Antennas for Communications Engineering - Thornton, John, 1968-; Huang, Kao-Cheng (Piscataway, NJ : IEEE Press ; Hoboken, New Jersey : Wiley, 2013)
The aim of this book is to present the modern design principles and analysis of lens antennas. It gives graduates and RF/Microwave professionals the design insights in order to make full use of lens antennas. Why do we want to write a book in lens antennas? Because this topic has not been thoroughly publicized, its importance is underestimated. As antennas play a key role in communication systems, recent development in wireless communications would indeed benefit from the characteristics of lens antennas: low profile, and low cost etc.
"Lens antennas--why and how they should be used more often in modern communications systems. This remarkable work provides RF/microwave engineers with complete guidance on how to develop lens antennas, focusing on recent advances in communications engineering where this often overlooked technology is especially useful. It clearly demonstrates the benefits of using lens antennas in modern communication systems, featuring numerous examples, measurement data, fabrication techniques, and real-world applications. Modern Lens Antennas for Communications Engineering explores many types of lens antennas in great detail, from polyrods and low sidelobe antennas to the spherical lens and hemispherical lens-reflector scanning antennas. In addition to design principles and computational techniques, readers will find a host of helpful tips on how to fabricate lens antennas in small batches for assessment, choose the right dielectric material, configure measurement campaigns, and tackle practical issues when constructing antennas and measuring their properties. The book provides information on: Economically coupling a millimeter-wave circuit into a radiating beam whose polarization and shape is tightly controlled; Utilizing costly spectrum in cellular networks beamed to the ground from platforms high in the upper atmosphere; Tracking two different satellites from a single terminal on a high-speed train. Modern Lens Antennas for Communications Engineering is an excellent resource for RF/microwave engineers, designers, and researchers in academia and industry, and anyone wishing to learn how to take full advantage of lens antennas and their many useful and interesting properties."--Publisher's description.
1. INTRODUCTION / John Thornton and Kao-Cheng Huang -- 1.1. Lens Antennas: An Overview -- 1.2. Feeds for Lens Antennas -- 1.3. Luneburg and Spherical Lenses -- 1.4. Quasi Optics and Lens Antennas -- 1.5. Lens Antenna Design -- 1.6. Metamaterial Lens -- 1.7. Planar Lens or Phase-Shifting Surface -- 1.8. Applications -- 1.9. Antenna Measurements -- 2. REVIEW OF ELECTROMAGNETIC WAVES / Kao-Cheng Huang -- 2.1. Maxwell's Equations -- 2.2. Antenna Parameters -- 2.3. Polarization -- 2.4. Wave Propagation in Metamaterials -- 3. POLYROD ANTENNAS / Kao-Cheng Huang -- 3.1. Polyrods as Resonators -- 3.2. The Polyrod as a Radiator -- 3.3. Patch-Fed Circular Polyrod -- 3.4. Array of Polyrods -- 3.5. Multibeam Polyrod Array -- 4. MILLIMETER WAVE LENS ANTENNAS / Kao-Cheng Huang -- 4.1. Millimeter Wave Characteristics -- 4.2. Millimeter Wave Substrate Lens for Imaging -- 4.3. Millimeter Wave and Submillimeter Wave Lens -- 4.4. Analysis of Millimeter Wave Spherical Lens -- 4.5. Waveguide-Fed Millimeter Wave Integrated Lens -- 5. LENS ANTENNAS FOR COMMUNICATIONS FROM HIGH-ALTITUDE PLATFORMS / John Thornton -- 5.1. Introduction -- 5.2. The High-Altitude Platform Concept -- 5.3. Advantages of Lenses over Reflector Antennas -- 5.4. Development of a Shaped Beam Low-Sidelobe Lens Antenna with Asymmetric Pattern -- 5.5. Lens Antenna Payload Model -- 5.6. Multifeed Lens -- 5.7. Multiple Beam Spherical Lens Antennas for HAP Payload -- 6. SPHERICAL LENS ANTENNAS / John Thornton -- 6.1. Introduction -- 6.2. Spherical Lens Overview -- 6.3. Analytical Methods -- 6.4. Spherical Lens Materials and Fabrication Methods -- 6.5. Revisiting the Constant-Index Lens -- 6.6. Cross-Polarization Properties of Spherical Lenses -- 7. HEMISPHERICAL LENS-REFLECTOR SCANNING ANTENNAS / John Thornton -- 7.1. Introduction -- 7.2. Candidate Scanning Antenna Technologies -- 7.3. Spherical and Hemispherical Lens Antenna -- 7.4. Hemispherical Lens Prototype -- 7.5. Evolution of a Two-Layer Stepped-Index Polymer Lens -- 7.6. A Hemispherical Lens-Reflector Antenna for Satellite Communications -- 7.7. A Low-Index Lens Reflector for Aircraft Communications / Contribution by D. Gray -- About the Authors -- Index.
Includes bibliographical references and index.
Print version record and online resource; title from PDF title page (IEEE Xplore, viewed April 23, 2014).
Keywords: Lens antennas; TECHNOLOGY & ENGINEERING -- Electronics -- General; TECHNOLOGY & ENGINEERING -- Telecommunications; Lens antennas; Electronic books; Electronic books